Quality of service-based selection model for Software as-a-Service in small and medium enterprises - Ogunrinde, Rowland Rotimi (2019)
Enterprise applications (EAs) are known to assist organizations achieve operational excellence and competitive advantage. Small and Medium Enterprises (SMEs) which are the major drivers of most thriving global economies use the on-premise EAs which are known to be costly. This creates business challenge of competitively thriving in the same market environment with their large enterprise counterparts. The advent of Cloud computing (CC) offers the SMEs opportunity of accessing cheap cloud-hosted EA services delivered as Software-as-a-Service (SaaS) on pay-per-use basis bypassing huge initial capital. However, existence of numerous Cloud Service Providers (CSPs) offering Cloud EAs leaves a challenge of selecting a suitable and cost-efficient provider of application that is based on meeting the SMEs’ customized Quality of Service (QoS) requirements. More so, the excessively large number of QoS attributes on which the CSPs are assessed can be derailing to the selection suitability quest of the SMEs. Therefore, the objectives of this study are to explore the selection criteria, analyze the attributes that are relevant and important to the SMEs to avoid overlapping functionalities, and to propose a QoS based model for SaaS selection in the SME. Seven selection criteria and 179 QoS attributes were identified from the literature while 29 QoS attributes emerged after analysis using sharing and combination process, and this forms the basis of the research hypotheses. Consequently, a confirmation study was conducted which includes a review by panel of experts, a pilot study and an empirical study. The result of the empirical study indicates the degree of importance of the selection criteria and attributes forming the basis of derivation of the selection criteria’s Global Weight of Factor (GWF) utilized in the SaaS selection process. The hypothetical relationships were tested using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The proposed model known as Quality of Service based Selection Model (QSSM) for SaaS consists of service request, service selection criteria with their attributes, and the Cloud enterprise selection process where weighting, ranking and cost-based comparison takes place to make the final ranking based on service suitability and cost. A prototype named as QSS System is developed and validated by expert review panel and users to indicate its feasibility and acceptability. Results show that QSS system is beneficial in selecting suitable and cost-effecient CSP. Research findings indicate that the QSSM achieved an acceptable fit with six of the seven main hypotheses. The proposed model provides a comprehensive analysis of important selection criteria while making investment decisions from the SMEs’ perspectives. This study also contributes to the practical insights into achieving service selection suitability with a model that tends to minimize the gap between the SMEs’ QoS requirements and the characteristics of the system by considering the QoS importance rating for selection. Incorporation of cost-efficiency selection component in the model is a step further that will help cut cost for the SMEs adopting the Cloud.